(untitled) (Research Nepal Journal of Development Studies, 2019)
The number of Nepali NGOs is on the rise. However, except the total number of NGOs, the information about the spatial distribution of these NGOs is rarely available. This descriptive paper utilizes the data from the Social Welfare Council and Aid Management Platform of the Ministry of Finance to explore the spatial distribution of NGOs and foreign aid in Nepal. It uses descriptive statistics and visual graphs and charts to demonstrate the distribution. The study finds that NGOs and foreign aid are agglomerated in province number three of Nepal. The paper suggests that the uneven distribution of NGOs and aid leads to uneven realization of development outcomes in Nepal. Registration, renewal, and procedures are extremely lengthy and tedious in Nepal.